Kepastian Hukum Terhadap Penilai Publik Sebagai Penentu Nilai Hak Cipta Dalam Jaminan Kredit Di Indonesia - Waluja, Hana Djaja (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2021)
The purpose of this research is to unravel and analyze the restrictions used by banking institutions with the non-inclusion of copyright as one of credit warranty objects, and to unravel and analyze the legal certainty of public appraisals in assessing copyright as a credit warranty. The methods used in this research are normative juridical by using the basis of analysis of legislation, as well as using statute and conceptual approaches. Based on the results of research and discussion, credit warranty can include copyright as an object through the fiduciary guarantee scheme, but its existence is still not followed by the trust of the banking institutions so it is necessary to enact the strengthen of copyright with public appraisal institutions as sponsors for copyright assessment in banking institutions. In Copyright Act, fiduciary guarantee can include copyright an object. This is good news for the development of the creative economy, but the banking world is not yet clear in its execution, this then creates a void and contradictions between laws and regulations.